Multiplexed Bioassays: Dual‐Encoded Microbeads through a Host–Guest Structure: Enormous, Flexible, and Accurate Barcodes for Multiplexed Assays (Adv. Funct. Mater. 34/2016). (12th September 2016) - Zhang, Ding Sheng‐zi; Jiang, Yang; Yang, Haiou; Zhu, Youjie; Zhang, Shunjia; Zhu, Ying; Wei, Dan; Lin, Ye; Wang, Pingping; Fu, Qihua; Xu, Hong; Gu, Hongchen
Abstract : Dual‐encoded microbeads with host–guest structures can be designed as barcodes for bead‐based suspension arrays, as described by H. Xu, H. Gu, and co‐workers on page 6146. Precise and flexible tuning of fluorescence intensity through controlled preparation results in a barcode library with enormous encoding capacity. Barcodes fixed with capturing succeed in recognizing specific target analytes and demonstrate to be a multiplexed bioassay platform with excellent prospects.